2006
DOI: 10.1524/ract.2006.94.12.825
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(VI) sorption onto kaolinite in the presence and absence of humic acid

Abstract: We studied the U(VI) sorption onto kaolinite in batch experiments in the absence and presence of humic acid (HA) under different experimental conditions: [U]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(107 citation statements)
references
References 43 publications
9
96
0
2
Order By: Relevance
“…The decreased U adsorption at pH > ~7.5 is due to competition between dissolved HA, carbonate, and U-carbonate complexes for adsorption onto surface sites, where observed HA adsorption remains high at pH up to 9.5, particularly for SRS sediment and goethite ( Figure S-1). Kaolinite features point of zero charge (PZC) at around pH 5 (18,22).…”
Section: Resultsmentioning
confidence: 99%
“…The decreased U adsorption at pH > ~7.5 is due to competition between dissolved HA, carbonate, and U-carbonate complexes for adsorption onto surface sites, where observed HA adsorption remains high at pH up to 9.5, particularly for SRS sediment and goethite ( Figure S-1). Kaolinite features point of zero charge (PZC) at around pH 5 (18,22).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, U has a strong binding affinity for NOM, both soluble and insoluble fractions. Soluble HA can complex U(VI), increasing its solubility and reducing its ability to adsorb onto Fe oxides and clays at circumneutral pH (Křepelová et al, 2006). Natural organic matter can also affect the rate and extent of U sorption onto silica sand (Tinnacher et al, 2013).…”
Section: Effect Of Natural Organic Matter On Redox Processesmentioning
confidence: 99%
“…Complexation of U(VI) with HA is strongest between pH 4.5 and 7 in the presence of dissolved inorganic carbon (pCO 2 at least 10 À3.5 atm). At low and high pH (<3 or >8.5), HA can increase adsorption to mineral surfaces, possibly due to low solubility of HA at low pH and the presence of U(VI)-carbonate-HA ternary surface complexes at high pH (Lenhart and Honeyman, 1999;Křepelová et al, 2006;Payne et al, 1996). The presence of HA can affect U(IV) as well by increasing the solubility via the formation of aqueous U(IV)-HA species; increased rate of oxidation has been observed due to this complexation (Gu et al, 2005).…”
Section: Effect Of Natural Organic Matter On Redox Processesmentioning
confidence: 99%
“…Complete sorption of U onto clay and other surfaces typically occurs within a period of a few days [19]. Krepelova et al (2006) found that U(VI) adsorption to clay (kaolinite) under acidic conditions increases if humic acids are present due to the formation of additional binding sites for U coming from the adsorption of humic acids to kaolinite [20]. Feng et al (2005) showed in batch experiments that peat humic acid is sorbed to different clay minerals (kaolinite and montmorillonite) via cation bridging, ligand exchange and van der Waals forces.…”
Section: +mentioning
confidence: 99%